Trans-heterozygosity for mutations enhances the risk of recurrent/chronic pancreatitis in patients with Cystic Fibrosis - Valentina Maria Sofia; Cecilia Surace; Vito Terlizzi; Letizia Da Sacco; Federico Alghisi; Antonella Angiolillo; Cesare Braggion; Natalia Cirilli; Carla Colombo; Antonella Di Lullo; Rita Padoan; Serena Quattrucci; et al. (BMC, 2018)
Abstract Background Recurrent (RP) and chronic pancreatitis (CP) may complicate Cystic Fibrosis (CF). It is still unknown if mutations in genes involved in the intrapancreatic activation of trypsin (IPAT) or in the pancreatic secretion pathway (PSP) may enhance the risk for RP/CP in patients with CF. Methods We enrolled: 48 patients affected by CF complicated by RP/CP and, as controls 35 patients with CF without pancreatitis and 80 unrelated healthy subjects. We tested a panel of 8 genes involved in the IPAT, i.e. PRSS1, PRSS2, SPINK1, CTRC, CASR, CFTR, CTSB and KRT8 and 23 additional genes implicated in the PSP. Results We found 14/48 patients (29.2%) with mutations in genes involved in IPAT in the group of CF patients with RP/CP, while mutations in such genes were found in 2/35 (5.7%) patients with CF without pancreatitis and in 3/80 (3.8%) healthy subjects (p < 0.001). Thus, we found mutations in 12 genes of the PSP in 11/48 (22.9%) patients with CF and RP/CP. Overall, 19/48 (39.6%) patients with CF and RP/CP showed one or more mutations in the genes involved in the IPAT and in the PSP while such figure was 4/35 (11.4%) for patients with CF without pancreatitis and 11/80 (13.7%) for healthy controls (p < 0.001). Conclusions The trans-heterozygous association between CFTR mutations in genes involved in the pathways of pancreatic enzyme activation and the pancreatic secretion may be risk factors for the development of recurrent or chronic pancreatitis in patients with CF.